Respuesta :

The value of k is equal to -5.

           4x - 3y = -5
     -2(4x - 3y) = -2(5)
-2(4x) - 2(-3y) = 10
         -8x + 6y = 10
4x-3y = -5 -8x+6y=10

First off you'll have to start with the first half of the equation, 4x-3y=-5

So then you'll get,  -2(4x - 3y) = -2(5)

Now you'll have to fill it in with the new information -2(4x) - 2(-3y) = 10
         
This is the later half of the equation -8x + 6y = 10

 so leaving it all up to -5 when you place it all together! I hope this helped some, after it was broken down a bit! :)